Analisis Variasi Time Repetition (TR) terhadap Signal to Noise Ratio dan Contrast to Noise Ratio pada Pemeriksaan MRI Cervical T2 Weighted Fast Spin Echo (FSE) Potongan Sagital - Rini Indrati; Heriansyah Heriansyah; Wakhrudin Wakhrudin (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Time Repetition (TR) is one parameter that can affect the value of Signal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR). The purpose of this research is to know the effect of variation of TR value on SNR and CNR on cervical MRI examination with Sagital T2 Weighted Fast Spin Echo sequence and to know the most optimal TR value from the variation of TR value to SNR and CNR on cervical MRI examination with Sagital T2 Weighted Fast Spin Echo.Methods: The type of this study was experimental study. The study was conducted using MRI 1.5 Tesla at Kasih Ibu Denpasar Hospital. Data were 40 MRI cervical images of sagital Fast Spin Echo from 10 volunteers with four variations of TR (2500 ms, 3000 ms, 3500 ms, and 4000 ms). The SNR and CNR values are measured by identifying the Region of Interest (ROI) in the corpus, discus, cerebro spinal fluid (CSF), and medula spinalis regions to obtain the average signals and compared with the mean deviation of the background. Data was analyzed by regression test to know the influence and by Anova test.Results: The result of the research showed that there was the influence of TR value to SNR and CNR of MRI Cervical Sagital T2 FSE. There was a strong correlation between the variation of TR values with SNR and CNR Cervical with p-value 0.05, the optimal TR value obtained in Cervical Sagital T2 FSE anatomical image on MRI 1,5 Tesla modality was 3500 ms.Conclusion: Time Repetition affected the signal to noise ratio and contrast to noise ratio. TR 3500 ms produced the most optimal cervical MRI image quality.